2016
DOI: 10.9787/pbb.2016.4.4.426
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Seedling Vigor-Associated Quantitative Trait Loci in Temperate Japonica Rice

Abstract: A quantitative trait loci (QTL) analysis of seedling vigor traits was conducted under dry-seeded conditions using 176 recombinant inbred lines developed from a cross of two California temperate japonica rice varieties M-203 and M-206. Height at early seedling (HES) and height at late seedling (HLS) stage, growth rate (GR), and fresh weight were evaluated in a growth chamber. Assessment of HES, HLS, and GR was also performed in outdoor basins in 2015 and 2016. M-203 was significantly better for all traits in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Seedling vigor is controlled by many QTLs and is also one of several important agronomic traits for direct-seeding rice systems (Yano et al, 2012). During the last few decades, a large number of QTLs associated with seedling vigor have been identified (Cui et al, 2002;Zhang et al, 2005;Lu et al, 2007;Zhou et al, 2007;Cairns et al, 2009;Abe et al, 2012;Yano et al, 2012;Cheng et al, 2013;Diwan et al, 2013;Dang et al, 2014;Cordero-Lara et al, 2016;Singh et al, 2017;Zhang et al, 2017). Among these QTLs, only one major QTL for seedling height (SH) on the long arm of chromosome 3 has been finely mapped, and OsGA20ox1 is the most likely candidate gene at this locus (Abe et al, 2012;Yano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Seedling vigor is controlled by many QTLs and is also one of several important agronomic traits for direct-seeding rice systems (Yano et al, 2012). During the last few decades, a large number of QTLs associated with seedling vigor have been identified (Cui et al, 2002;Zhang et al, 2005;Lu et al, 2007;Zhou et al, 2007;Cairns et al, 2009;Abe et al, 2012;Yano et al, 2012;Cheng et al, 2013;Diwan et al, 2013;Dang et al, 2014;Cordero-Lara et al, 2016;Singh et al, 2017;Zhang et al, 2017). Among these QTLs, only one major QTL for seedling height (SH) on the long arm of chromosome 3 has been finely mapped, and OsGA20ox1 is the most likely candidate gene at this locus (Abe et al, 2012;Yano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, two single-locus mixed models, MLM and CMLM, and one multilocus mixed model, MLMM, were used to map QTL and identify SNP markers associated with seedling vigor and regrowth vigor traits. Morphological traits, such as shoot length, number of shoots and shoot dry weight, have been used previously to evaluate plant or seedling vigor in different crops, including wheat [10] and rice [15,26,27]. In the present study, winter wheat lines in the wheat diversity panel showed significant phenotypic variation in shoot length, number of shoots and shoot dry weight from both the initial growth and the regrowth of the plants.…”
Section: Discussionmentioning
confidence: 60%
“…Genome-wide association mapping can link genotype to phenotype in natural diversity populations for identifying natural allelic variations associated with traits of interest [19]. Over the years, GWAS has been successfully used to identify genomic regions associated with quantitative traits in different crop species, such as wheat [20][21][22][23], sorghum [24,25], rice [26][27][28], barley (Hordeum vulgare L.) [29,30] and maize (Zea mays L.) [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…with WCA traits present on 12 chromosomes [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] . Each study used different determinants to assess and identify genomic regions associated with WCA viz., shoot length, shoot weight, coleoptile length, shoot dry weight, leaf area and specific leaf area.…”
Section: Dynamic Expression Of Weed Competitive Qtls In Rice Severamentioning
confidence: 99%
“…To dissect the weed competitive traits in rice, QTL mapping has been employed and large number of QTLs for rice WCA traits 2 , 24 were identified using biparental segregating populations (F 2 , Backcross inbred line, double haploids, recombinant inbred lines) derived mainly from intrasub-specific 25 28 and inter-subspecific crosses 29 – 33 . Recently, association mapping panels 34 37 and SNP based genotyping by sequencing 38 40 have been employed. However, no efforts were done to exploit weed competitive QTLs from inherent weed competitive O. glaberrima species.…”
Section: Introductionmentioning
confidence: 99%